Eugenia uniflora Surinam Cherry: FPS-202/FP202, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the Surinam cherry (Eugenia uniflora), highlighting its characteristics, uses, and invasive potential in Florida. It describes the plant’s appearance, including its smooth, shiny, aromatic leaves, small white flowers, and ribbed red berries. The document also details its growth habits, soil and light requirements, and common uses in landscaping. Additionally, it addresses the plant’s invasive status in Florida, recommending its removal and discouraging its purchase. The document concludes with information on propagation, pests, and diseases associated with the Surinam cherry. Original publication date October 1999.